2011
DOI: 10.2166/wh.2011.087
|View full text |Cite
|
Sign up to set email alerts
|

Virus removal efficiency of Cambodian ceramic pot water purifiers

Abstract: Virus removal efficiency is described for three types of silver-impregnated, ceramic water filters (CWFs) produced in Cambodia. The tests were completed using freshly scrubbed filters and de-ionized (DI) water as an evaluation of the removal efficiency of the virus in isolation with no other interacting water quality variables. Removal efficiencies between 0.21 and 0.45 log are evidenced, which is significantly lower than results obtained in testing of similar filters by other investigators utilizing surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 5 publications
0
20
0
1
Order By: Relevance
“…Additionally, because of the negatively charged ceramic surface, CWFs with and without silver coating generally exhibit low affinity with virus and negatively-and non-charged chemical pollutants, resulting in negligible capture of these pollutants through adsorption as well. For example, previous studies reported that CWFs only had viral removal efficiencies in the range of 0.21 to 1.6 LRV in long-term testing (Brown and Sobsey, 2010;Salsali et al, 2011;van der Laan et al, 2014), with no significant differences between silver-impregnated and non-impregnated CWFs (van der Laan et al, 2014). The low removal efficiency for virus and various chemical pollutants represents a major challenge for conventional CWFs.…”
Section: Removal Of Various Classes Of Contaminantsmentioning
confidence: 99%
“…Additionally, because of the negatively charged ceramic surface, CWFs with and without silver coating generally exhibit low affinity with virus and negatively-and non-charged chemical pollutants, resulting in negligible capture of these pollutants through adsorption as well. For example, previous studies reported that CWFs only had viral removal efficiencies in the range of 0.21 to 1.6 LRV in long-term testing (Brown and Sobsey, 2010;Salsali et al, 2011;van der Laan et al, 2014), with no significant differences between silver-impregnated and non-impregnated CWFs (van der Laan et al, 2014). The low removal efficiency for virus and various chemical pollutants represents a major challenge for conventional CWFs.…”
Section: Removal Of Various Classes Of Contaminantsmentioning
confidence: 99%
“…Several studies have appeared using ceramic filters based on local low-cost raw materials for water purification in areas with scarce economic and water resources. The treated water was intended for human consumption, and the elimination of viruses, bacteria and other microorganisms was carried out through a simple gravitational filtration process [109][110][111]. One example is the work of Hasan et al, which applied a ceramic membrane based on local clay in a membrane biological reactor (MBR) for the removal of arsenic from groundwater in Bangladesh [51].…”
Section: Treatment Of Groundwater and Surface Water For Human Consumpmentioning
confidence: 99%
“…Much of the literature on ceramic filter studies, however, has been designed to look at the effectiveness of the filters, rather than the impact of the silver on the effectiveness (e.g. Baumgartner et al, 2007;Brown et al, 2008;Clasen et al, 2004Clasen et al, , 2005du Preez et al, 2008;Salsali et al, 2011). In addition to filters employing silver to improve microbial removal, domestic (and travel) filters may also incorporate silver into the filter to reduce biofilm formation, however, no published literature (in terms of silver efficacy) was found on this application.…”
Section: Silver-coated Ceramic Filter Applicationsmentioning
confidence: 99%